2021
DOI: 10.1155/2021/3444083
|View full text |Cite
|
Sign up to set email alerts
|

Corneal and Epithelial Thickness Mapping: Comparison of Enhanced Spectral-Domain- and Spectral-Domain-Optical Coherence Tomography

Abstract: Objective. To compare the results and repeatability of the corneal thickness (CT) and epithelial thickness (ET) maps provided by Swept-Source-Optical Coherence Tomography with those of Spectral-Domain-OCT in normal eyes. Methods. 30 normal eyes of 30 patients were assessed by 3 trained operators with SS-OCT and SD-OCT. Results. The central and minimum ET obtained with both devices were correlated: central ET, r = 0.86, p < … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 15 publications
1
9
2
Order By: Relevance
“…Unexpectedly, the TRTs at the nasal and temporal points at 1 mm are higher than those at 3 mm regardless of the stage of KC. Georgeon et al [ 40 ] studied the reproducibility of ET provided by MS-39 in normal eyes and found that the superior regions usually showed poor reproducibility, which differed from the findings in our study. The altered morphology of the KC could lead to lower reproducibility.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Unexpectedly, the TRTs at the nasal and temporal points at 1 mm are higher than those at 3 mm regardless of the stage of KC. Georgeon et al [ 40 ] studied the reproducibility of ET provided by MS-39 in normal eyes and found that the superior regions usually showed poor reproducibility, which differed from the findings in our study. The altered morphology of the KC could lead to lower reproducibility.…”
Section: Discussioncontrasting
confidence: 99%
“…After analysis, we attribute this to the irregularity of keratoconus, which would increase the uncertainty and difficulty of measurement. Moreover, the measurement error increases as the measuring point is further away from the corneal apex in our study, which is consistent with other studies [ 40 , 42 ]. This may be because the incident angle between the OCT probe beam and the corneal surface increases as the distance from the center of the cornea increases [ 40 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This instrument uses an 840-nm wavelength beam. We are aware that other specialized AS-OCTs by using a 1310-nm wavelength could be more performing (Georgeon et al, 2021). Anyway, RTVue-100 allowed us to detect detailed scans of the corneal healing process and its improvements over time.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the type of commercially available anterior-segment OCT strategy, studies have confirmed the excellent measurement repeatability and reproducibility of this imaging modality [13,14]. Recently, Kundu et al introduced an artificial intelligence-driven model for detecting early keratoconus.…”
Section: Medical Hypothesis Discovery and Innovation In Optometry Dea...mentioning
confidence: 99%